To combine like terms in the equation 5x - 12 - 6x = -10x + 7 - 1, we need to simplify each side of the equation separately and then combine the like terms.
On the left-hand side:
5x - 12 - 6x simplifies to -x - 12.
On the right-hand side:
-10x + 7 - 1 simplifies to -10x + 6.
Now, the equation becomes -x - 12 = -10x + 6.
To combine the like terms, we can add x to both sides of the equation:
(-x + x) - 12 = (-10x + x) + 6.
Simplifying further:
-12 = -9x + 6.
To isolate the variable, we can subtract 6 from both sides of the equation:
-12 - 6 = -9x + 6 - 6.
Simplifying further:
-18 = -9x.
Finally, to solve for x, we can divide both sides of the equation by -9:
-18 / -9 = -9x / -9.
Simplifying further:
2 = x.
Therefore, the combined like terms form of the equation 5x - 12 - 6x = -10x + 7 - 1 is x = 2.
What Is 5x−12−6x=−10x+7−1 When Combined Like Terms
1 answer